Influência do hipotireoidismo gestacional experimental (HGE) sobre a resposta inflamatória da prole submetida a um modelo de asma alérgica - Prado, Marina Inês de Oliveira (2019)
During intrauterine life, the fetus needs adequate conditions for its correct development. If some insult or different stimulus occurs, physiological and metabolic physiological and metabolic adaptations that may have negative repercussions in the adult life of this individual. This concept is known as fetal programming. It is known that the fetus depends thyroid hormones for its correct growth. These exert essential essential physiological actions in the functioning of biological systems, with emphasis on the development of the immune system. Based on studies that have shown that experimental gestational hypothyroidism (EGH) alters the immune response and that adverse conditions during intrauterine development are important predictors of susceptibility to the development susceptibility to the development of allergic diseases such as asthma, the objective of this to investigate the influence of HGE on the inflammatory response of offspring subjected to allergic asthma. HGE was induced in pregnant Swiss mice by the administration of Methimazole 0.02% in the drinking water, from the 9th gestational day until the day of delivery. To verify the influence of HGE on lung inflammation, offspring from hypothyroid (PMH) and (PME) mothers were subjected to an animal model of allergic asthma induced by egg albumin-induced allergic asthma (OAI). The data obtained were expressed as mean ± standard error of the mean (S.E.P.M.). Analyses were performed using two-way ANOVA, followed by Bonferroni's post-test. Bonferroni post-test. The critical level set was 5%. The PMH-OVA showed lower total number of cells in the bronchoalveolar lavage (BAL) (p < 0.001); there was also less myeloperoxidase myeloperoxidase (MPO) activity in the lung (p < 0.001) and lower eosinophilic peroxidase content in the BAL (p < 0.001). in BAL (p < 0.05), compared to PME-OVA. It is concluded that HGE had an inhibitory effect on total leukocyte recruitment to the bronchoalveolar lavage (BAL), lung MPO MPO activity in the lung and eosinophilic peroxidase content in the BAL of the offspring subjected to the of allergic asthma induced by egg albumin